Pengaruh Pertumbuhan Penjualan, Intensitas Modal, Ukuran Perusahaan Dan Komisaris Independen Terhadap Penghindaran Pajak - Sianturi, Bernaderti; Andar Febyansyah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This study aims to examine the relationship between sales growth, capital intensity, company size and independent commissioners on tax avoidance. Using purposive sampling method on a population of companies that meet the criteria of 13 health industry companies listed on the IDX for the period 2020-2023 with 52 financial reports. Descriptive analysis and multiple linear regression are the data analysis tools used with the use of the SPSS version 29 data processing application. Tax avoidance as the dependent variable proxied by the Effective Tax Rate (ETR) is measured by the ratio between income tax expense and profit before tax. Sales growth is calculated by subtracting the current year's sales from the previous year's sales, and dividing by the previous year's sales. Capital intensity is measured by the ratio of total assets to total sales. Company size is calculated by Natural Logarithm (LN) multiplied by the company's total assets. Independent commissioners are calculated by the total independent commissioners divided by the total members of the board of commissioners. The results show that simultaneously sales growth, capital intensity and independent commissioners have a positive effect on tax avoidance. Partially, the variables of sales growth, capital intensity and company size do not produce a significant effect on tax avoidance; while the independent commissioner variable has a significant effect on tax avoidance